Healthy organizational culture – healthy employees? Effectiveness of organizational culture on perceived health of German police officers - Jablonowski, Lara (International journal of police science & management, 2017)
The purpose of this study was to examine the effects on individual perceived health of the factors organizational culture, working conditions, physical and mental health, and presenteeism, as moderated by lifestyle factors. A detailed comparison was made between the uniformed police division and the criminal investigation department to explore their perceptions of the supportiveness of their subcultures, working conditions and perceived health. Survey responses, obtained through an online questionnaire, from 258 officers from German police forces showed significant differences in perception. Uniformed officers evaluated their working conditions more positively compared with officers from the criminal investigation department, resulting in a more positively rated perceived health for the uniformed police division. Results showed that the more a police organizational culture fostered their subcultures and health-enhancing working conditions, the higher the perceived physical and mental health. Implications for research and practice are discussed.